JURIDICAL ANALYSIS OF VICTIMS OF THE ECONOMIC EXPLOITATION OF CHILDREN UNDER THE AGE TO REALIZE LEGAL PROTECTION FROM HUMAN RIGHTS ASPECTS: RESEARCH STUDY AT THE OFFICE OF SOCIAL AND COMMUNITY EMPOWERMENT IN BATAM CITY - Geovani, Iwoeng; Nurkhotijah, Siti; Kurniawan, Harry; Milanie, Feby; Nur Ilham, Rico (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
the Aspect of Human Rights (Research Study at the Office of Social Affairs and Community Empowerment), has been carried out as it should, in accordance with Law Number 35 of 2014 concerning Amendments to the Law Number 23 of 2002 concerning Child Protection (Supplementary Gazette of the State Gazette of 2014 Number 5606). The qualification/type of writing in this journal uses normative legal writing, and subsequently integrates it with sociological/empirical legal writing, and to analyze some of the problems in this journal, Satjipto Rahardjo's big theory of legal protection, Jeremy Bentham's middle theory, while Soerjono Soekanto's application/applied theory. The results of the field analysis show that legal protection for children as victims of economic exploitation has not been effective. This means that there are obstacles/obstacles in its implementation, including the obstacles faced in dealing with the problem of violence and economic exploitation of children, namely law enforcement in controlling children, not solving the root problem, only taking curative action, not preventing it. For this reason, it is hoped that the government together with law enforcers will pay more attention and take firm action regarding the problem of economic exploitation of street children, both in terms of guidance and legal sanctions for perpetrators of economic exploitation.